The Communication Between Intestinal Microbiota and Ulcerative Colitis: An Exploration of Pathogenesis, Animal Models, and Potential Therapeutic Strategies - Hu, Yu; Ye, Zhen; Wu, Mingquan; She, Yingqi; Li, Linzhen; Xu, Yujie; Qin, Kaihua; Hu, Zhipeng; Yang, Maoyi; Lu, Fating; Ye, Qiaobo (Frontiers in Medicine, 2021)
Ulcerative Colitis (UC) is a chronic inflammatory bowel disease. The prolonged course of UC and the lack of effective treatment management make it difficult to cure, affecting the health and life safety of patients. Although UC has received more attention, the etiology and pathogenesis of UC are still unclear. Therefore, it is urgent to establish an updated and comprehensive understanding of UC and explore effective treatment strategies. Notably, sufficient evidence shows that the intestinal microbiota plays an important role in the pathogenesis of UC, and the treating method aimed at improving the balance of the intestinal microbiota exhibits a therapeutic potential for UC. This article reviews the relationship between the genetic, immunological and microbial risk factors with UC. At the same time, the UC animal models related to intestinal microbiota dysbiosis induced by chemical drugs were evaluated. Finally, the potential value of the therapeutic strategies for restoring intestinal microbial homeostasis and treating UC were also investigated. Comprehensively, this study may help to carry out preclinical research, treatment theory and methods, and health management strategy of UC, and provide some theoretical basis for TCM in the treatment of UC.